PENGARUH BRAND IMAGE DANKUALITAS PELAYANAN TERHADAP PENINGKATAN PENJUALAN DI CV PURWASARI MOTOR - Sari, Sindang; Ayu, Pretty (STIE DWI SAKTI BATURAJA, 2024)
This research aims to determine the impact of brand image and service quality on sales growth at CVPurwasari Motor, a spare parts outlet and car service provider. The study sample consisted of 84 customers.Data analysis used multiple regression with a determination coefficient of 0.130 or 13.00%. The variablesof brand image (X1) and service quality (X2) affect sales growth (Y), while the remaining 87.00% isinfluenced by other factors not examined. These results are supported by a significance value of 0.023 <0.05. Service quality significantly influences sales growth, as evidenced by a significance value of 0.026 <0.05.